CAPILLARY BLOOD FLOW STATE ESTIMATION DURING PATIENTS TREATMENT WITH ORTODENTIC MECHANICAL APPLIANCES - D. A. Domenyuk; A. G. Karslieva; E. G. Vedeshina; S. V. Dmitrienko; A. S. Kochkonyan; Yu. S. Arutyunyan (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Laser Doppler flowmetry was used to investigate the palatal muscosa capillary bloodflow in children aged 4.5-9 years with crowded teeth undergoing treatment with removable orthodontic appliances from cold-cured base polymers. The results obtained from the examination of the capillary blood flow based on the amplitude standard deviation, the variation coefficient, the amplitudes of vasomotor, breathing, and cardiorhythms, as well as the indices for active and passive mechanisms of blood flow modulation at the areas under study, showed that the hemodynamics indices in the palatal muscosa got disturbed a month after the treatment was started while the disturbances went even worse at later stages